Neonatal infections: Case definition and guidelines for data collection, analysis, and presentation of immunisation safety data. Issue 49 (1st December 2016) - Vergnano, Stefania; Buttery, Jim; Cailes, Ben; Chandrasekaran, Ravichandran; Chiappini, Elena; Clark, Ebiere; Cutland, Clare; de Andrade, Solange Dourado; Esteves-Jaramillo, Alejandra; Guinazu, Javier Ruiz; Jones, Chrissie; Kampmann, Beate; et al.
Abstract: Maternal vaccination is an important area of research and requires appropriate and internationally comparable definitions and safety standards. The GAIA group, part of the Brighton Collaboration was created with the mandate of proposing standardised definitions applicable to maternal vaccine research. This study proposes international definitions for neonatal infections. The neonatal infections GAIA working group performed a literature review using Medline, EMBASE and the Cochrane collaboration and collected definitions in use in neonatal and public health networks. The common criteria derived from the extensive search formed the basis for a consensus process that resulted in three separate definitions for neonatal blood stream infections (BSI), meningitis and lower respiratory tract infections (LRTI). For each definition three levels of evidence are proposed to ensure the applicability of the definitions to different settings. Recommendations about data collection, analysis and presentation are presented and harmonized with the Brighton Collaboration and GAIA format and other existing international standards for study reporting.